The Influence of Qur’an Memorization Learning on the Quality of Students’ Qur’an Memorization - Mukhammad Mukhammad; Abdul Talib Bin Bon (At-tadzkir: Islamic Education Journal, 2026)
Qur’an memorization (tahfidz) is one of the flagship programs in Integrated Islamic Junior High Schools (SMPIT), aiming to shape a Qur’anic-characterized generation while improving students’ memorization quality. This study aims to analyze the effect of Qur’an memorization learning on students’ memorization quality at SMPIT in Batam City, focusing on SMPIT Ulil Albab, SMPIT Fajar Ilahi, and SMPIT El-Yasin. The research method employed was quantitative with an ex post facto approach. The sample consisted of 90 students selected using purposive sampling. The results showed that tahfidz learning had a positive and significant effect on students’ memorization quality. A regression coefficient of 7.09 and an R² value of 0.80 indicated that approximately 80% of the variation in memorization quality could be explained by the intensity of tahfidz learning, while the remaining variation was influenced by other factors such as motivation, family support, and psychological conditions. Improvements identified included recitation accuracy, tajwid application, fluency, and retention through regular muroja’ah practice. Thus, the tahfidz program has proven effective in improving the memorization quality of SMPIT students in Batam City, although further reinforcement is still needed in aspects of time management and individual mentoring.